The role of legislation and consumer perception in shaping circular economy behaviour - Milosevic, Isidora Miloje; Plotnic, Olesea; Dumančić, Kosjenka; Bojkovska, Katerina (Serbian Journal of Management, 2025)
The concept of the circular economy (CE) brings about significant and radical changes in consumption patterns, especially in the habits and decisions of consumers, who are key participants in this model. Understanding how organisational barriers, laws, and circular economy strategies affect consumer preferences in the circular model can help manufacturers develop efficient and profitable strategies that respond to market needs and encourage sustainable consumption. Therefore, the paper aims to examine how personal, organisational, and financial barriers affect circular economy strategies and perceptions of them to achieve the effect of legislation on consumer decisions regarding sustainable consumption, consumer behaviour, and support for circular initiatives. The results of empirical research have shown that all proposed hypotheses are accepted, with a special emphasis on the impact of legislation on consumer decisions, which can significantly shape consumer behaviour in sustainable consumption and provide incentives for the circular economy. Based on the influence of factors, this paper can serve as a roadmap for decision-makers in creating regulations and for consumers to participate actively in circular initiatives towards sustainable consumption
Keywords: circular economy; customer behaviour; sustainable production; legislation